The role of gut microbiota in hepatitis B disease progression and treatment. Issue 2 (30th August 2021) - Chen, Bryan; Huang, Harry; Pan, Calvin Q.
Abstract: Current therapeutic interventions can only suppress hepatitis B virus (HBV) replication or reduce complications without a cure. Therefore, further development of new treatment methods is critical for the global eradication of HBV. Accumulating evidence suggests that the liver and gut share an interconnected relationship referred to as the 'Gut‐Liver Axis', where exchanges happen bi‐directionally. The gut itself is the host to a unique microbiota profile which has metabolic, immunological, neurological and nutritional functions. Gut microbiota is not only constantly intersecting with the liver but also associated with hepatic injury when dysbiosis occurs. In recent years, there has been increased interest in gut microbiota and its implications on liver disease treatment. Progress has been made in understanding the complex relationship between chronic hepatitis B (CHB) and gut microbiota. New investigative techniques such as colony‐free sequencing enabled new perspectives into this field. Mouse models and human studies revealed that HBV infection is associated with significant alteration of gut microbiota, which differ depending on the stage of CHB disease progression. Different mechanisms of the hepatic injury from gut microbiota dysbiosis have also been proposed based on findings of increased intestinal permeability to toxins, disruption of normal bacterial metabolism, and colonization of the gut by oral microbiota. New treatment methods targeting gut microbiota in CHB, such as probiotics and faecal microbiota transplant, have also gained promising results in recent years. The current review recapitulated the most recent investigations into the relationship between gut microbiota and CHB to provide research directions towards the new therapeutic target of CHB.